Nam tour of duty - Knox, Terence (Middlesex : New World Video, 1987)
Vietnam 1967, a platoon goes on a hazardous mission to destroy a hidden NVA base. Led by Anderson, a war-weary sargeant and Goldman, a green lieutenant, they find themselves outnumbered and outgunned, their initiation into the deadly reality of jungle combat is harrowing ... their chances of survival, uncertain. This is the story of bravo compan
Terence Knox ... (et al.)
Keywords: Vietnamese Conflict, 1961 -- 1975 -- Motion pictures and the conflict; War films; War films and programs